Vivienda para adultos mayores, parque, centro medico: edificio de vivienda para adultos mayores edificio perenne (2020)
The developed project is part of the Nueva Alameda Entreparques urban renewal plan. The work block is developed through the design of two different uses, which respond to physical determinants of the context, such as, population characteristics of the area and the relationship with the linear park of the renovation plan. In the first place, as the main element of the block, a housing building for the elderly is developed. This building with an architectural typology of a bar with a simple gallery is located on the most privileged side of the block, offering the best visuals, optimal solar incidence and, urban accessibility and direct connection with public activities that take place in the neighborhood. The building has suites fully equipped for the elders, which are grouped in such way that they can generate small communities among the inhabitants of the building and thus, create relationships between users of the building. In turn, the building has communal...